Prevalence and Predictors of Occupational Health Hazards among Nurses Working in Health Care Facilities at Moshi Municipal, Kilimanjaro, Tanzania (Tanzania Medical Journal, 2022)
BackgroundHealth care workers in sub-Saharan Africa have higher exposure to disease causing pathogens than those working in high income countries. Occupational health hazards remain one of the under looked challenges in low-income countries. Nurses carry out most of the hazardous activities since they spend more time with patients than any other medical personnel.            AimTo assess the prevalence and predictors of occupational health hazards faced by nurses working at Moshi municipal.MethodsThis study was a hospital based descriptive cross-sectional study done at four health facilities of different levels at Moshi municipal. The study population was 215 nurses who were interviewed face to face using questionnaire. Obtained data was processed using SPSS version 20. For analysis of predictors for occupational health hazards the crude odds ratio, adjusted odds ratio and P-value with their corresponding 95% Confidence Intervals were calculated by comparing with exposures to occupational health hazards.ResultsOut of 215 participants, 169 (78.6%) reported to have experienced biological hazards. 171 (79.5%) experienced non-biological hazards. The key exposures to biological hazards were needle stick injuries (prevalence of 43, 20%), and blood drop and splash exposure (prevalence of 122, 56.7%). The most prevalent non – biological hazards were low back pain (132, 61.4%), and work-related stress which included verbal abuse (118, 54.9%) and physical abuse (27, 12.5%). 116 (54%) reported shortage of personal protective equipment in their facilities. The key predictors of experiencing biological hazards were hours of working per week (p=0.03), type of facility one is working (p=0.01), number of years at work (p=0.02) and age of the participant (p=0.03). Predictors of experiencing non-biological hazards were carrying the patient (p=0.01) and standing for more than 3 hours (p=0.01) ConclusionPrevalence of occupational health hazards among nurses in Moshi municipal is high. This is influenced by many working hours per week, shortage of personal protective equipment, inadequate training on occupational health hazard prevention, and working at higher level health facility. Younger nurses and nurses with few years at work are at higher risk of experiencing needle stick injuries.